2020 15th IEEE International Conference on Automatic Face and Gesture Recognition (FG 2020) 2020
DOI: 10.1109/fg47880.2020.00009
|View full text |Cite
|
Sign up to set email alerts
|

How are attributes expressed in face DCNNs?

Abstract: As deep networks become increasingly accurate at recognizing faces, it is vital to understand how these networks process faces. While these networks are solely trained to recognize identities, they also contain face related information such as sex, age, and pose of the face. The networks are not trained to learn these attributes. We introduce expressivity as a measure of how much a feature vector informs us about an attribute, where a feature vector can be from internal or final layers of a network. Expressivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Open questions remain about how to optimize models of the visual processing of faces. In the present study, and in others ( Colón et al., 2021 ; Dhar et al., 2020 ; Hill et al., 2019 ; Parde et al., 2017 , 2019 ), face representations were built from deep learning algorithms trained explicitly to separate identities. In other work (Yildirim et al., 2020) , networks have been trained to simultaneously decode an array of face parameters from images (i.e., shape and texture coefficients from a three-dimensional computer graphics model of faces, along with illumination direction and pose angle).…”
Section: Discussionmentioning
confidence: 96%
“…Open questions remain about how to optimize models of the visual processing of faces. In the present study, and in others ( Colón et al., 2021 ; Dhar et al., 2020 ; Hill et al., 2019 ; Parde et al., 2017 , 2019 ), face representations were built from deep learning algorithms trained explicitly to separate identities. In other work (Yildirim et al., 2020) , networks have been trained to simultaneously decode an array of face parameters from images (i.e., shape and texture coefficients from a three-dimensional computer graphics model of faces, along with illumination direction and pose angle).…”
Section: Discussionmentioning
confidence: 96%
“…This process becomes even more challenging when derived data representations are considered, i.e., templates. As shown by recent work [59], [60], contemporary biometric templates encode a variety of information that is entangled in the features and, therefore, difficult to remove or hide in a selective manner.…”
Section: Biometric Privacy Enhancementmentioning
confidence: 99%
“…Recently, Dhar et al [120] found that age-related information is highly coupled with identity-salient features in the latent space of a well-trained face recognition model [121]. The entanglement of these attributes has been exploited by Deb et al [113], who trained an autoencoder that operates directly within the latent space of a pre-trained face recognition model, such as CosNet [114].…”
Section: Child Vs Adult Face Ageingmentioning
confidence: 99%